URGENSI SAINS DALAM PENERAPAN PETUNJUK AL-QUR’AN DAN HADITS (ANALISIS TERHDAP METODE PENENTUAN ARAH KIBLAT, HISAB RUKYAH DAN WAKTU SHALAT DALAM ILMU FALAK) - Muhammad Arsad Nasution (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The verses of the Qur'an and the Hadith of the Prophet are the main guidelines for determining the direction of Qibla in performing prayers, the times for praying five times a day and night, and determining the beginning of the month of Ramadan, the beginning of Sawal, and Eid al-Adha. Under certain conditions the Qibla direction, prayer times and the start of Ramadan and Sawal, can be determined easily manually. However, in conditions that are far apart and the natural conditions are not always sunny, the determination of the times of worship cannot be done manually. In this condition, the verses of the Qur'an and the hadith of the Prophet SAW cannot be used as independent benchmarks to determine the times of worship above, but he needs modern science to help make it easier to determine the times of worship. This conditions encourages the emergence of falakiyah scientists who combine science and syara' in determining the Qibla direction, prayer times, and determining the beginning of Ramadan and Shawwal.